2013
DOI: 10.1213/ane.0b013e318290c542
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Identification of Gastroesophageal Reflux Disease as a New Risk Factor for Surgical Site Infection in Cerebral Palsy Patients After Spine Surgery

Abstract: We show that GERD increases the risk for infection in CP patients after spine fusion. Prospective multicenter studies are necessary to further validate the predictive value of this risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Furthermore patients with CP have a more severe degree of scoliosis with greater Cobb angles and need for extended spinal fusions. All these factors may play a role in the higher risk for postoperative complications (10,14,23). In the multivariate risk factor analysis for our cohort, we found a 13 times higher risk for postoperative pneumonia in patients with epilepsy.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore patients with CP have a more severe degree of scoliosis with greater Cobb angles and need for extended spinal fusions. All these factors may play a role in the higher risk for postoperative complications (10,14,23). In the multivariate risk factor analysis for our cohort, we found a 13 times higher risk for postoperative pneumonia in patients with epilepsy.…”
Section: Discussionmentioning
confidence: 52%
“…Twelve studies included posterior approaches to surgery only, 33 studies included posterior approaches or combined/staged anterio‐posterior approaches, while approach was not reported, or was not defined for participants with CP, in six studies. Length of follow‐up varied greatly among the studies and all except for five studies did not state measurement time points or they were not standardized. Only six studies reported any missing data or loss to follow‐up .…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies reported preoperative factors for poor postoperative outcomes; however, only 11 of these reported statistical associations or correlations separately for CP samples (Table SIV, online supporting information) . Comorbidities including gastrointestinal issues, respiratory conditions, seizures, malnutrition, intellectual disability, reduced speech ability, and prior surgical infection were identified as risk factors in addition to an increased weight, older age, higher preoperative platelet or white cell count, and the type or severity of preoperative spinal or pelvic deformity.…”
Section: Resultsmentioning
confidence: 99%
“…In children treated with us the esophagus biopsy is not an action that is still being protocols and has not been performed. It should be taken in account that the diagnosis of esophagitis does not interfere with interventionism (21). On the other hand, fibrogatroscopy and more esophageal biopsy in young children is an action that requires special susceptibility and a special technical skill (22).…”
Section: Discussionmentioning
confidence: 99%